Pengaruh Kualitas Pelayanan, Disiplin Kerja, Komunikasi Interpersonal dan Fasilitas Pelayanan Terhadap Kepuasan Masyarakat - Khariri, Lulu’ Endah; Suryani, Nanik (Universitas Negeri Semarang, 2020)
This study aims to determine the effect of service quality, work discipline, personal communication, and service facilities at the Population and Civil Registry Office of Pemalang Regency. The population in this study were all visitors to the Population and Civil Registry Office of Pemalang Regency, totaling 7,326,263 people. The sampling technique in this study uses iteration sample techniques, with a total of 115 visitors. Methods of data collection using questionnaires, documentation, and interviews. The results of multiple linear regression analysis showed the equation Y = 11,086 + 0,80 X1 + 0,202 X2 + 0,107 X3 + 0,107 X4 + e. The magnitude of influence simultaneously between competence, service quality, work discipline, interpersonal communication to community satisfaction by 18.6%. The variable that gave the biggest contribution was service facilities which amounted to 4.3%, followed by work discipline variables which amounted to 4.16%, then interpersonal communication amounted to 3.92%, and service quality amounted to 4.16%.